Safety of anti-TNFa biological drugs - G. Valentini; F. Trotta (PAGEPress Publications, 2011)
Objective: To analyse TNF-a antagonists (infliximab, etanercept e adalimumab) side effects published in the literature. Methods: Review of published studies on this matter. Results: The main side effects reported include severe infections (even though such a risk is increased per se in RA patients), possible reactivation of a previous tuberculosis, development of opportunist germs infections (mainly those with granulomas development as Aspergillus, Cryptococcus e Histoplasma). During therapy with both infliximab and etanercept development and reactivation of demyelisating diseases have been described, sometimes associated with permanent disability. Congestive heart failure, even in the absence of predisposing risk factors, development of lymphoma, mainly non-Hodgkin, and few cases of pancytopenia with hypocellular bone marrow have also been reported. Conclusions: Since comparison studies on the 3 TNF-a antagonists have not been performed yet, at present it is not possible to suggest using one drug out of the three in different clinical conditions; undoubtedly, the safety profile represents a major criterion to choose the more appropriate drug in the daily clinical practice.